Type I and III interferons shape the retinal cytokine network and barrier function in an in vitro model of ocular toxoplasmosis - Geiller, Benjamin; Greigert, Valentin; Hillenbrand, Caroline A.; Gommenginger, Chloé; Beal, Laetitia; Brunet, Julie; Filisetti, Denis; Villard, Odile; Denis, Julie; Pfaff, Alexander W. (Frontiers in Immunology, 2023)
The particularities of the ocular immune environment and its barrier protection in the context of infection are not well elucidated. The apicomplexan parasite Toxoplasma gondii is one of the pathogens successfully crossing this barrier and establishing chronic infection in retinal cells. As a first approach, we studied the initial cytokine network in vitro in four human cell lines: Retinal pigmented epithelial (RPE), microglial, astrocytic and Müller cells. Furthermore, we looked at the consequences of retinal infection on the integrity of the outer blood-retina barrier (oBRB). We particularly focused on the roles of type I and type III interferons, (IFN-β and IFN-λ). Especially IFN-λ is known for its significant role in barrier defense. However, its effect on the retinal barrier or T. gondii infection remains unexplored, unlike IFN-γ, which has been extensively studied in this context. Here, we show that stimulation with type I and III interferons did not limit parasite proliferation in retinal cells we tested. However, IFN-β and IFN-γ strongly induced inflammatory or cell-attracting cytokine production, whereas IFN-λ1 showed less inflammatory activity. Concomitant T. gondii infection influenced these cytokine patterns, distinctly depending on the parasite strain. Interestingly, all these cells could be stimulated to produce IFN-λ1. Using an in vitro oBRB model based on RPE cells, we observed that interferon stimulation strengthened membrane localization of the tight junction protein ZO-1 and enhanced their barrier function, in a STAT1-independent manner. Together, our model shows how T. gondii infection shapes the retinal cytokine network and barrier function, and demonstrates the role of type I and type III interferons in these processes.